2011
DOI: 10.1002/andp.201100067
|View full text |Cite
|
Sign up to set email alerts
|

Exact solution of the ion‐laser interaction in all regimes

Abstract: We show that in the trapped ion-laser interaction all the regimes may be considered analytically. We may solve not only for different laser intensities, but also away from resonance and from the Lamb-Dicke regime. It is found a dispersive Hamiltonian for the high intensity regime, that, being diagonal, its evolution operator may be easily calculated

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…It has been shown already that for low intensities it is possible also to consider the ion micromotion [26], and by using Ermakov-Lewis invariant methods [30,31,32] it was possible to linearize the ionlaser Hamiltonian when the micromotion was included [44]. Here, we follow Zúñiga et al [45] and show how it is possible to solve the ion-laser interaction in different regimes, including high intensity and medium intensity.…”
Section: Solution In Different Regimes: Dispersive Hamiltoniansmentioning
confidence: 97%
See 1 more Smart Citation
“…It has been shown already that for low intensities it is possible also to consider the ion micromotion [26], and by using Ermakov-Lewis invariant methods [30,31,32] it was possible to linearize the ionlaser Hamiltonian when the micromotion was included [44]. Here, we follow Zúñiga et al [45] and show how it is possible to solve the ion-laser interaction in different regimes, including high intensity and medium intensity.…”
Section: Solution In Different Regimes: Dispersive Hamiltoniansmentioning
confidence: 97%
“…In Section 3.1, we showed that the ion-laser Hamiltonian (45) can be casted in the form given by expression (48) by means of the similarity transformation (46). Therefore, we have linearized the ionlaser interaction in an exact way, by means of a unitary transformation; i.e., both Hamiltonians,Ĥ ion andĤ ion are equivalent.…”
Section: Different Regimesmentioning
confidence: 99%
“…(4.20b). For practical purpose, let us consider the initial condition | (0) = | | , then, the solution at second order is given by | ( ) , = (2) , cos( taken from Eq.16 and Eq.18 of reference [36], which is the small rotation approximation solution for this system and where high = − 2 2 /2 in the case of high intensity regime. Hence, using Eq.…”
Section: Second Order Correctionmentioning
confidence: 99%
“…taken from Eq.16 and Eq.18 of reference [36], which is the small rotation approximation solution for this system and where high = − 2 2 /2 in the case of high intensity regime. Hence, using Eq.…”
Section: Comparison Of the Perturbative Solution With The Small Rotat...mentioning
confidence: 99%